Changes of body composition and anaerobic performance after rapid weight loss in taekwondo players - Kijin, K.; Wookwang, C. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
This study examined the difference of changes on body composition and anaerobic high-intensity performance after rapid weight loss following a different weight class in male taekwondo players. A significant change of body composition in central region after rapid weight loss through energy restriction and sauna was found and it could be suggested the compound change of skinfold and muscle by the preferential change of body circumferences as compared to body fat. Although body composition showed a significant change in heavy weight group, light weight group showed a serious depression of anaerobic high-intensity performance. In these results, it was suggested that light weight group was asked a more careful attention on the negative effects of energy restriction and dehydration in rapid weight loss.